PENGEMBANGAN INSTRUMEN TES HASIL BELAJAR KETERAMPILAN DASAR BERMAIN BULUTANGKIS - Hambali, Burhan (2015)
Penelitianinibertujuanuntukmengembangkandanmemperolehinstrumenteshasilbelajarketerampilandasarbermainbulutangkis (ITHB KDBB).Instrumenteshasilbelajarinimerupakansalahsatubentukperformance testdengan model individual perfomanceassessment yang dapatmengukurkemampuanparasiswadanatlitsekolahbulutangkissetelahmengikuti proses pembelajaranataulatihan, khususnyapadaketerampilandasarbermainbulutangkis (servistinggi, lob bertahan, dropsotdansmes)yang dikembangkankedalamjenissubjective rating test danaccuracy-based test. Penelitiandilakukandenganmenggunakanmetoderesearch and development (R&D) dandilaksanakankedalamdelapantahaputamayaituMenentukanatributlatenatau domain tes yang akandiukur, Analisistujuanpembuatantes, Batasanpadatesyang akandikembangkan, Penyusunanspesifikasiisiataukisi-kisi instrument,Spesifikasi format, Perencanaanujicobadanseleksi item,Perencanaanmengumpulkan data normatif, sertaPengujian manual danbahanpendukung.Hasilujicobateroritik yang dilakukanolehparaExpert JugdmentmemperolehnilaikoefisienvaliditasisidenganteknikanalisisCVR terentangantara 0.60 sampaidengan 1.00, sedangkanpadapengujianempirikdilakukanpadasiswasekolahbulutangkisFPOK UPI usia 11-13 tahun, dandilakukandalamdua kali ujicoba, ujicobatahappertamadilakukanpada 15 siswasedangkanujicobakeduadilakukanpada50 siswa. Hasilpengujianreliabilitasdanvaliditas ITHB KDBB final yang dilakukanpadaujicobakeduamemperolehnilaiestimasireliabilitasstabilitasdengantekniktest-retestsebesar 0.96 (servistinggi), 0.91 (lob bertahan), 0.89 (dropshot) dan0.89 (smesh) serta0.96 (ITHB KDBB Keseluruhan). Sedangkanpadaestimasireliabilitaskonsistensi internal denganteknikinter-rater reliability (objektifitas) model IntraclassCoefisienCorelasi (ICC) memperolehkoefisienreliabilitassebesar 0.98 (servistinggi), 0.95 (lob bertahan), 0.95 (dropshot), 0.96 (smesh), dan 0.96 (ITHB KDBB keseluruhan). Kemudianpadapengujianvaliditas ITHB KDBB menggunakanvaliditasprediktifdengankriteriahasilrangkingsiswaatauatlitdenganmenggunakanteknikround robin atauhasilpertandingansetengahkompetisidiperolehnilaikoefisienvaliditasprediksisebesar 0.70 (servistinggi), 0.69 (lob bertahan), 0.71(dropshot), 0.74 (smesh), dan 0.75 (ITHB KDBB keseluruhan).BerdasarkanhasilpengujianreliabilitasdanvaliditasdapatdisimpulkanbahwaITHB KDBB yangdikembangkansudahreliabeldan valid dalammengukurketerampilandasarbermainbulutangkisuntuksiswadanatlitusia11-13 tahun. Kata Kunci : Instrumen, KDBB, Perfomance Assessment,Reliabilitas, Validitas. This study aims to develop as well as acquire a learning outcome instrument of badminton basic skill (ITHD KDBB). This instrument is one of the performance test forms promoting individual performance assessment learning model which is able to measure students' and athletes' badminton skills after they have gone through the processes of learning or training. Those skills concerning particularly on basic ones such as high serve, clear lob, dropshot, and smash are developed through subjective rating test and accuracy-based test. The method employed in this study is research and development (R&D) carried out within eight main sessions determining the test domain to measure, the analysis of the test making objective, the limitation of the test developed, the arrangement of specific content, the arrangement of specific format, the plan of test piloting and item selection, the plan of normative data collection and the test of manuals and supporting items. This ITHB KDBB is tested both theoretically and empirically. In terms of theoretical side conducted through experiment judgment, it is found that its validity coefficient tested using CVR analysis range between 0.60 and 1.00. Whereas, in terms of empirical side tested to students FPOK UPI of badminton club at the age of 11-13 years old carried out twice (the first one joined by 15 student and the second one joined by 50 of them), here are the results. The reliability and validity results of ITHB KDBB using test-retest technique are 0.96 (high serve), 0.91 (clear lob). 0.89 (dropshot), 0.89 (smash), and 0.96 (the whole ITHB KDBB). However, the consistency estimation of reliability using inter-rater reliability (objectivity) promoting Intraclass Correlation Coefficient (ICC) model consists of the following results: 0.98 (high serve), 0.95 (clear lob), 0.95 (dropshot), 0.96 (smash), and 0.96 (the whole ITHB KDBB). In the meantime, the test of ITHB KDBB validity using predictive validity test comprising students raking criteria with round robin comes up with the following results 0.70 (high serve), 0.69 (clearlob), 0.71 (dropshot), 0.74 (smash), and 0.75 (the shole ITHB KDBB). Based on those test results, it can be conclude that ITHB KDBB being developed is either reliable or valid to measure students', particularly 11-13 year-olds, badminton basic skills. Kata Kunci : ITHB KDBB, Performance Test, Performance Assessment, Reliability, Validity.